Effect of source and level of foliar zinc application on its concentration in grain , growth and Rice yield variety alyasmin ( Oryza Sativa L. ) . - جاسم رحيم علوان هلول (Journal of Kerbala for Agricultural Sciences, 2015)
A field experiment was conducted at Al – Mishkhab rice research station in Al – Najaf Governorate during summer season 2013 to study the effects of sources and levels of Zinc foliar applications on Zinc concentration in grain and growth of rice (Oriza sativa L.) Yasmin variety . Treatments included two sources of Zinc ( ZnSo4.7H2O ( 23 % ZN ) and Zn- EDTA ( 14 % Zn ) ) with ( 40 , 80 , 120) mg.zn.L-1 for foliar application . further to control treatment ( without Zinc ) . RCBD was conducted with three replicates . The following results were obtained: There is no significant effect for Zinc sources on all studied parameters. The levels of Zinc application had significant effect on most studied parameters with second level (80 mg. zn. L-1) having the most effect giving highest grain yield (5688 kg.h-1), the higher straw yield ( 6488 kg .h-1 ) and the higher zinc concentration in grain ( 35 mg Zn.kg-1 grain). The level 40 mg Zn.L-1 gave the highest height of plant( 89.8 cm) and highest number of spike ( 397 Spike.m-2). The interaction between sources & levels of Zinc application affected significantly in grain yield (6110 kg.h-1 ), number of spike ( 413 spike .m-2 ), straw yield ( 7263 kg .h-1 ) and zinc concentration in grain ( 36 mg Zn.kg-1 grain).